2023
DOI: 10.1021/acsami.3c00124
|View full text |Cite
|
Sign up to set email alerts
|

Directional Carrier Transport in Micrometer-Thick Gallium Oxide Films for High-Performance Deep-Ultraviolet Photodetection

Abstract: Incorporating emerging ultrawide bandgap semiconductors with a metal–semiconductor–metal (MSM) architecture is highly desired for deep-ultraviolet (DUV) photodetection. However, synthesis-induced defects in semiconductors complicate the rational design of MSM DUV photodetectors due to their dual role as carrier donors and trap centers, leading to a commonly observed trade-off between responsivity and response time. Here, we demonstrate a simultaneous improvement of these two parameters in ε-Ga2O3 MSM photodete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Followingly, 3 weeks after the fabrication of GaS based photodetector, the Raman spectrum measurement has been repeated and the measurement result is presented in figure 4(b). The emergence of the oxide peaks in the Raman spectrum can be implied from this figure, which is in accordance with the previous studies [22].…”
Section: Resultssupporting
confidence: 93%
“…Followingly, 3 weeks after the fabrication of GaS based photodetector, the Raman spectrum measurement has been repeated and the measurement result is presented in figure 4(b). The emergence of the oxide peaks in the Raman spectrum can be implied from this figure, which is in accordance with the previous studies [22].…”
Section: Resultssupporting
confidence: 93%
“…Fine-tuning the interdigitated electrode’s width, spacing, and active area allows for precise impedance and capacitance output adjustments. As demonstrated by H. Pandya and W. Zhang et al, employing a spacing of 10 μm as opposed to 30 μm yields a remarkable ~69% increase in the disparity of impedance between benign and cancerous breast tissue samples [ 48 , 49 ]. These results inspired us to define our electrode geometry with an electrode width of 10 um and spacing of 10 um.…”
Section: Resultsmentioning
confidence: 99%
“…T. Dong and W. Zhang et al demonstrated a correlation between the initial capacitance and the number of active finger pairs. As the number of active finger pairs increases, the initial capacitance also increases, indicating a higher density of electrical field lines over the sensing area [ 49 , 50 ]. Based on these findings, we decided to design our electrode with a small footprint area (1.13 mm 2 ) sufficient to integrate with microfluidic channels and sensitivity sufficient to detect biphasic droplets.…”
Section: Resultsmentioning
confidence: 99%
“…However, these two properties typically oppose one another. [97,138] Zhang et al [97] proposed a LM + x composite mixture, wherein a co-doped TIM consisting of liquid metal and Cu in a silicone matrix yielded a thermal conductivity of 3.94 WmK -1 and an elastic modulus of 699 kPa. The performance of this specific TIM was better in comparison to that of the single-phase TIMs, due to the synergistic effects of the highly thermally conductive Cu and the liquid metal fillers, which have very little impact on the mechanical properties of the matrix material.…”
Section: Thermal Propertiesmentioning
confidence: 99%